Fermentation of xylose, arabinose, glucose, their mixtures and sugarcane bagasse hydrolyzate by yeast Pichia stipitis for ethanol production - Natthanon Phaiboonsilpa; Teerin Chysirichote; Verawat Champreda; Navadol Laosiripojana (Energy Reports, 2020)
Xylose, arabinose and glucose were studied their fermentabilities to ethanol by yeast Pichia stipitis. The experiments were conducted by using 1.0, 5.0, 10.0 and 20.0 g/l of mono-saccharide solutions in a close fermentation system at 30 °C with 100-rpm shaking rate for 120 h. Fermentabilities of mono-saccharides appeared to produce high ethanol yield when a low concentration of xylose and arabinose was applied. Glucose fermentability was, however, found to be preferable at high sugar concentration. The highest ethanol yields could be achieved at 106.27, 86.25, and 73.10%, reported as a relative % to its theoretical ethanol yield, by using 1.0 g/l of xylose, 1.0 g/l of arabinose, and 20.0 g/l of glucose solutions, respectively. The empirical equations were then established based on the fementabilities obtained to predict ethanol yield for a given concentration of mono-saccharides. A comparative study on fermentation of the mono-saccharide mixture and sugarcane bagasse hydrolyzate, of which xylose, arabinose and glucose concentrations were similar, were moreover conducted. It was revealed that the empirical equations provided an excellent estimation of ethanol concentration when the mono-saccharide mixture was used. The presence of furans and other compounds in sugarcane bagasse hydrolyzate besides the mono-saccharides, however, resulted in a lower ethanol fermentability compared with that calculated by the empirical equations. This is due apparently to an inhibition effect of these additional components to Pichia stipitis.
Keywords: 330; Arabinose; Bioethanol; Glucose; Hydrolyzate; Pichia stipitis; Sugarcane bagasse; Xylose